Development in low-temperature solid oxide fuel cells based on thin-film materials - Опахай, С; Кутербеков, К; Соловьев, А; Нуркенов, С; Ныгыманова, А (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
Solid oxide fuel cell is one of the most promising technologies for providing efficient and environmentally friendly energy production for a wide range of applications. At present, an important problem in the development of a solid oxide fuel cell is a decrease in the operating temperature by reducing the thickness of the electrolyte, since the internal resistance of the cell decreases and its power increases. An effective solution to this problem is the use of thin-film materials, both for electrolytes and for electrodes (cathode, anode). This paper provides a review of literature data that discusses new thin-film materials for electrodes and electrolytes of low-temperature solid oxide fuel cells with brief conclusions on the research topic.